DEVELOPING STUDENTS’ KNOWLEDGE FROM THE RESULTS OF SCAFFOLDING IN ENGLISH TEACHING - Diah Gusrayani (University of Kuningan, 2014)
Abstract: Some issues of the difficulties of teaching English in Indonesia have significantly revealed and analyzed by some researchers (Nurweni, 1997; Moedjito and Harumi, 2008) and the issues have provoked some studies to anchor several solutions for teachers to consider (Supriadi and Hoogenboom, 2004; Thalal, 2010). In Indonesia, the issue has also been thoroughly investigated. This paper attempts to reveal the problems of teaching English experienced by 2 junior high school teachers in Sumedang along with the alternative solution namely scaffolding concept which has been widely investigated and believed as appropriate tool mediation for children to learn English with particular difficulties hampered: culture, teachers’ background, quantity and quality of teaching and similar causes (Vygotsky, 1962; Tudge, 1992; Stone, 1998; Kong, 2002; Donovan and Smolkin, 2002). This concept of scaffolding is considered in this research as a bridge to a better understanding of the requirements of curriculum 2013 that students have to possess knowledge (K3) specifically factual, conceptual and procedural knowledge having experienced the learning. As students are conditioned to achieve these skills: remembering, understanding, implementing, analyzing, synthesizing, evaluating and producing, at that pinpoint the presence of scaffolding concept in English teaching is an inevitable strategy to be applied. Keywords: scaffolding, students’ knowledge (K3), curriculum 2013, tool mediation, metacognitive.